Agricultural Markets and Risks : Management of the Latter, Not the Former - Varangis, Panos; Larson, Donald; Anderson, Jack R. (World Bank, Washington, DC, 2013)
The authors review the historical relationship between the work of applied economists, and policymakers, and the institutions that came to characterize the commodity, and risk markets of the 1980s. These institutions were a response to the harmful consequences of commodity market volatility, and declining terms of trade. But the chosen policies, and instruments relied on market interventions, to directly affect prices, or the distribution of prices in domestic, and international markets. For practical, and more fundamental reasons, this approach failed. The authors next discuss how a growing body of work, contributed to a change in thinking that moved policy away from stabilization goals, toward policies that emphasized the management of risks. They distinguish between the macroeconomic effects of volatile commodity markets, and the consequences for businesses, and households. The authors argue that both sets of problems remain important development issues, but that appropriate policy instruments are largely separate. Nonetheless, because governments, households, and firms must all respond to a wide range of sources of risk, they emphasize the role for an integrated policy by government. Increasingly, alternative approaches have come to rely on market-based instruments. Such approaches accept the market view of relative prices as immutable, but address directly the negative consequences of volatility. As traditional risk markets (such as futures and insurance markets) expand, and new parametric markets emerge, the practicality of applying market-based instruments to traditional risk, and development problems increases. The authors show the change in approaches to risk, and the reliance on old, and new market instruments, with new, and sometimes experimental programs, with special emphasis on programs at the World Bank.